Invitro Activity of Mineral Trioxide Aggregate Modification from Rice Hull Ash Silica and Calcium Oxide from Clamshells - Yuliatun, Leny (BERKALA SAINSTEK, 2024)
The impact of SrO particles and hydroxyapatite (HA) on the characteristics of Mineral Trioxide Aggregate (MTA) from silica Rice Husk Ash (RHA) and Precipitated Calcium Carbonate (PCC) from clam shell has been studied in this research. Silica and calcium oxide are used as material to form tricalcium silicate (C3S) and dicalcium silicate (C2S) in MTA. Bi2O3 and SrO were added in MTA with 18% (w/w) total percentage. MTA was made with a sol-gel process and used catalyst NH3. After synthesis, material was calcined at 1000 oC for 3 h. HA was added at percentages of 3, 6, and 9% in 5% SrO modified MTA to see the effect of its addition on the material. The modified MTA (MTA-SrO-HA) were hydrated water using water to powder method with ratio of 3:1. The MTA-SrO5/HA6 showed higher compressive strength and dentine interaction to the commercial MTA (Proroot brand) in days 3 and 7. This material had potential as a root canal filling in dental endodontic treatment.